2004
DOI: 10.1136/adc.2003.034033
|View full text |Cite
|
Sign up to set email alerts
|

Association of parental eczema, hayfever, and asthma with atopic dermatitis in infancy: birth cohort study

Abstract: Objective: To evaluate the association of parental history of atopic disease with childhood atopic dermatitis, and to examine the relative strength of associations with maternal and paternal disease. Design: Mothers were recruited to the Avon longitudinal study of parents and children (ALSPAC) from the eighth week of pregnancy. Before parturition, both parents were asked, separately, to report their lifetime history of eczema, asthma, and hayfever. Parents reported symptoms of atopic dermatitis in their childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 23 publications
7
60
2
1
Order By: Relevance
“…AR is an atopic condition similar to atopic dermatitis and has been shown to cluster among families [9]. The risk of children developing allergic disease increases by up to 4-fold if either parent has an atopic condition, particularly the mother [10,11,12,13,14,15,16,17]. Presently there are few reports describing the association between maternal AR and asthma in the context of atopy developing in the offspring, despite extensive studies examining maternal history of asthma or atopy.…”
Section: Introductionmentioning
confidence: 99%
“…AR is an atopic condition similar to atopic dermatitis and has been shown to cluster among families [9]. The risk of children developing allergic disease increases by up to 4-fold if either parent has an atopic condition, particularly the mother [10,11,12,13,14,15,16,17]. Presently there are few reports describing the association between maternal AR and asthma in the context of atopy developing in the offspring, despite extensive studies examining maternal history of asthma or atopy.…”
Section: Introductionmentioning
confidence: 99%
“…Also the relationship between IgE and SCORAD in AD patients shows that IgE can be used as a severity index of AD in patients and this correlation is stronger in patients with asthma. Some studies revealed that male sex, increasing age and family history of allergic disease contributed to an increased risk of each allergic disease 14,16,25 and family history of allergy was associated with a high risk of developing asthma. 6 There was a significant association between disease severity and eosinophil count.…”
Section: Discussionmentioning
confidence: 98%
“…In epidemiologic terms higher IgE antibody levels also appear to be associated with a more severe disease phenotype and worse long-term prognoses. 18 Maternal transmission of AD Parent-of-origin effects are thought to play an important role in the cause of AD (and other atopic conditions) because infant disease risk is often, 8,19,20 although not always, 9,21 found to be more closely related to maternal than paternal disease status. This observation might be related to a number of underlying mechanisms, including genomic imprinting, mitochondrial transmission, and gene-environment interactions involving the in utero environment and/or exposure to the immunologic and nutritional properties of breast milk.…”
Section: Ad and Atopymentioning
confidence: 98%
“…This is supported by the observation that parental history of AD represents a more potent risk factor for AD in a child than either asthma or allergic rhinitis. 8,9 Current evidence indicates that AD is strongly genetic, with enhanced levels of phenotype concordance reported in monozygotic relative to dizygotic twin pairs (0.72-0.77 vs 0.15-0.23). 2,3 The individual genetic factors or genes that contribute to the trait's cause are relative to other complex genetic diseases proving amenable to identification.…”
mentioning
confidence: 97%